Active Motor Card As A Solution For Physical Education Evaluation: A Review Of Sports And Health Physical Education Teachers Professional Education Graduates From The State University Of Malang - Winarno, Mashuri Eko; Fadhli, Nurrul Riyad; Yudasmara, Dona Sandy; Hariadi, Imam; Taufik; Aji, Galih Purnomo; Alfani, Muhammad Aliffajaruddin (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service aims to introduce and train the use of the Active Motor Card as an effective physical education evaluation tool for PJOK teachers who graduated from PPG State University of Malang. Evaluation in physical education often faces obstacles, such as time constraints and the complexity of measuring students' motor skills. Active Motor Card is presented as an innovative solution that can simplify the assessment process and provide accurate and structured results. This activity involves intensive training for PJOK teachers to understand the concepts, techniques for using and implementing evaluations using the Active Motor Card in the school environment. The methods used include theoretical presentations, direct practice, and question and answer sessions. The results of the activity showed that teachers felt better prepared to carry out comprehensive and accurate evaluations of students' motor skills. This is in accordance with the results of the pre-post test carried out by the teacher showing a significance level of <0.1. This program is expected to become a model for the development of physical education evaluation in various schools.